11.361 sports injuries in a 15-year survey of a Level I emergency trauma department reveal different severe injury types in the 6 most common team sports - Krutsch, Werner; Krutsch, Volker; Hilber, Franz; Pfeifer, Christian; Baumann, Florian; Weber, Johannes; Schmitz, Paul; Kerschbaum, Maximilian; Nerlich, Michael; Angele, Peter (Sportverletzung · Sportschaden, 2018)
Introduction Severe sports-related injuries are a common affliction treated in Level I trauma departments. Detailed knowledge on injury characteristics from different medical settings is essential to improve the development of injury prevention strategies in different team sports.Methods Team sport injuries were retrospectively analysed in a Level I trauma department registry over 15 years. Injury and treatment data were compared with regard to competition and training exposure. Injury data such as “time of visitation”, “type of injury”, “multiple injured body regions” and “immediate hospitalisation” helped to define the severity level of each team sports injury.Results At the Level I trauma department, 11.361 sports-related injuries were seen over 15 years, of which 34.0 % were sustained during team sports. Soccer injuries were the most common injuries of all team sports (71.4 %). The lower extremity was the most affected body region overall, followed by the upper extremity. Head injuries were mainly seen in Ice hockey and American football and concussion additionally frequently in team handball. Slight injuries like sprains or contusions occurred most frequently in all team sports. In soccer and team handball, injuries sustained in competition were significantly more severe (p < 0.001) than those sustained in practice.Volleyball and basketball had a trend to higher rate of severe injuries sustained during practice sessions.Conclusion Depending on the specific injury profile of each team sports, injury prevention strategies should address competitive as well as training situations, whichmay need different strategies.
Keywords: injury; team sports; football; emergency department; injury severity; injury prevention